Mineralogy and geochemistry of the argentiferous Pb-Zn and Cu veins of the Colakli area, Elazig, Eastern Turkey - Sağıroğlu, Ahmet; Şaşmaz, Ahmet (My University, 2004)
The studied Pb–Zn and Cu veins occur as N–S trending and vertically dipping features in quartz diorite of Coniacian–Campanian Elazig Magmatic Complex. The complex has characteristics typical of arc magmatism and is composed of granitoids and, volcanic, subvolcanic and pyroclastic rocks. The veins are 0.5–2.5 m. thick and their lengths reach up to 750 m. The ore of veins are either massive or disseminated in gangue of carbonate minerals, quartz and barite. The veins display two sets of mineral assemblages: (1) Pb–Zn veins are composed of galena, freibergite, barite, sphalerite, chalcopyrite, pyrite, a Pb–Cl phase and native silver; (2) Cu veins have a mineral association of chalcopyrite, pyrite, galena, sphalerite, cubanite, bismuthinite and fahlore. The ore bodies are accompanied by narrow but intensely developed wall rock alterations of argillization, carbonatization and silicification. Chemical analyses of ore samples indicate high Pb, Ag, Sb, Zn, Ba and Cu contents in the veins and high correlation values between Pb– Ag, Pb–Ba, Pb–Zn, Sb–Ag, Cd–Sb and Ba–Cd. The REE geochemistry points to ore deposition under acidic conditions and probably as a product of the final stages of magmatism. Field, microscopic and geochemical data also indicate that the ores are related to the last phases of the magmatic activity of the Elazig Magmatic
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Ag–Pb–Cu veins; Eastern Turkey; Elazig magmatic complex; Freibergite; Pb–Cl phase